2016
DOI: 10.4103/2231-0762.195510
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis, fluoride in urine, and nutritional status in adolescent students living in the rural areas of Guanajuato, Mexico

Abstract: Objective:The aim of this study was to assess urine fluoride concentration, nutritional status, and dental fluorosis in adolescent students living in the rural areas of Guanajuato, Mexico.Materials and Methods:A cross-sectional study was conducted including participants aged 11–20 years. The presence and severity of dental fluorosis was registered according to the Thylstrup and Fejerskov index (TFI) criteria. Anthropometric measures were also recorded. Urine sample of the first morning spot was recollected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…The average level of fluoride in urine of boys was higher than in drinking water which may be an outcome of additional ingestion of fluoride via intake of tea, milk, vegetables, etc. Similar observations of higher F − in urine have been made in other studies too (Paez and Dapas 1983;Szymaczek and Lewicka 2005;Rango et al 2014;Del Carmen et al 2016) ascribing the reason to additional intake of bioavailable fluoride through food. Based on the survey for dental fluorosis, it was observed that majority of the subjects suffered from dental fluorosis with the degree of expression varying from nil to severe through mild and moderate as per Dean's Index.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The average level of fluoride in urine of boys was higher than in drinking water which may be an outcome of additional ingestion of fluoride via intake of tea, milk, vegetables, etc. Similar observations of higher F − in urine have been made in other studies too (Paez and Dapas 1983;Szymaczek and Lewicka 2005;Rango et al 2014;Del Carmen et al 2016) ascribing the reason to additional intake of bioavailable fluoride through food. Based on the survey for dental fluorosis, it was observed that majority of the subjects suffered from dental fluorosis with the degree of expression varying from nil to severe through mild and moderate as per Dean's Index.…”
Section: Resultssupporting
confidence: 75%
“…Some studies (García-Pérez et al 2013;Del Carmen et al 2016) have reported prevalence of dental fluorosis in school children of younger age groups of 8-12 years and 12-15 years as well. Therefore, monitoring of urinary fluoride concentration is a useful tool to assess the exposure particularly among the children at places with problem of endemic fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…We used linear regression to evaluate the relationship between each of the biological measures of fluoride and concentrations of fluoride in community water. We controlled for the following potential confounders: maternal age [14,15] smoking status [16,17], BMI [18], gestational age at the time of sample collection, and race/ethnicity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…According to our findings, the low UFE observed (Maguire et al, 2013) during monitoring of fluoridated milk programmes may therefore be related to the effect of moderate physical activity, that children undertake during their breaks, on F absorption and excretion. F concentrations in blood and urine have been shown not to be influenced by sex (Torra et al, 1998;Del Carmen et al, 2016) However, due to the possible different physiological responses following exercise in children compared to adults, as well as females compared to males, further work is required to determine the effects of exercise on F metabolism in young children and different sexes. These findings can help inform the evidence base for stakeholders and decision makers in dental public health as well as health professionals who may wish to review F dose and time of administration in different fluoridation programmes.…”
Section: Discussionmentioning
confidence: 99%